Kepatuhan Mahasiswa Profesi Kedokteran Gigi Terhadap Pencegahan Penularan COVID-19 di RSGM - P FKG USAKTI - Goalbertus; C Panjaitan, Caesary; Gisella, Ivana (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: The characteristics of dental practice make the risk of cross-transmission of COVID-19 between dentists and patients higher, dental profession students also have a high risk of contracting COVID-19 because they interact directly with patients. Objective: To determine the compliance of dental profession students in preventing the transmission of COVID-19 at RSGM-P FKG Usakti. Method: This research is a cross-sectional descriptive observation using a questionnaire containing 20 statements filled out online involving 87 respondents. Results: The majority of students have used PPE according to standards, washed their hands using WHO's 6 steps, washed their hands 5 times and complied with the health protocols of the Indonesian Ministry of Health. Conclusion: The majority of students have complied with the protocol for preventing the transmission of COVID-19, but are still unable to maintain distance and avoid gathering and talking in groups.